The new Northwest Railway of Brazil (NOB) railway station in Bauru, an architectonic and political symbol of a strategic railway - Ghirardello, Nilson [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
The Northwest Railway of Brazil - NOB, built after 1905, constituted itself as a peculiar railway in relation to the others dedicated to coffee in Sao Paulo. It had an ambitious strategic purpose forged during the Empire, reduced in the Old Republic, however, vigorously resumed with the 1930 Revolution. Since then, the NOB, with ample resources, renewed administration and major works, will once again be one of the government's instruments to position itself strategically in South America. The main objective of this work; from a history of NOB and Brazilian railway constructions; is to show how the company's designs, during the Estado Novo, are physically expressed in the new headquarters station in Bauru. The architectural ensemble should reflect this path, expressed, above all, in the avant-garde reinforced concrete roof of the station, made entirely with national inputs and revolutionary for the time, symbol of the government's geopolitical strategy on the eve of the Second World War.
Keywords: NOB; Bauru; Estado Novo; Railway station; Architecture